2019
DOI: 10.1016/j.pragma.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Gaze and overlap resolution in triadic interactions

Abstract: This paper presents a corpus study on the role of gaze for overlap resolution in German and Dutch triadic interactions. The focus is on overlap due to a simultaneous start by two speakers with one speaker abandoning her TCU before reaching a point of completion. The gaze behaviours of all three participants in the conversations were recorded with mobile eye tracking glasses. The analysis of the eye tracking data reveals the following gaze patterns: speakers who prevail in the competition for the turn space use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…More specifically, Brône et al ( 2017 ) found this gaze pattern in 76% of cases and Eberhard and Nicholson ( 2010 ) reported this pattern in six out of seven speakers. Similarly, four other studies found that speakers do tend to terminate their gaze to indicate the turn hold (Kendon, 1967 ; Bavelas et al, 2002 ; Jokinen et al, 2013 ; Zima et al, 2019 ), which happens at Transition Relevance Place (TRP: Table 2 ), during switching pauses and hesitant markers (Jokinen et al, 2013 ; Brône et al, 2017 ). Jokinen et al ( 2013 ), concluded that eye gaze direction was a better predictor of turn hold than speech.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…More specifically, Brône et al ( 2017 ) found this gaze pattern in 76% of cases and Eberhard and Nicholson ( 2010 ) reported this pattern in six out of seven speakers. Similarly, four other studies found that speakers do tend to terminate their gaze to indicate the turn hold (Kendon, 1967 ; Bavelas et al, 2002 ; Jokinen et al, 2013 ; Zima et al, 2019 ), which happens at Transition Relevance Place (TRP: Table 2 ), during switching pauses and hesitant markers (Jokinen et al, 2013 ; Brône et al, 2017 ). Jokinen et al ( 2013 ), concluded that eye gaze direction was a better predictor of turn hold than speech.…”
Section: Resultsmentioning
confidence: 81%
“…All 29 studies used video recording to capture eye gaze during conversation, however nine did not specify how many cameras were used (Beattie, 1978 , 1979 ; Rutter et al, 1978 ; Goodwin, 1980 ; Harrigan, 1985 ; Egbert, 1996 ; Lerner, 2003 ; Park, 2015 ; Blythe et al, 2018 ). Seven studies used one camera for each participant (Lamb, 1981 ; Bavelas et al, 2002 ; Eberhard and Nicholson, 2010 ; Cummins, 2012 ; Ho et al, 2015 ; Holler and Kendrick, 2015 ; Ijuin et al, 2018 ), three studies used one camera for the whole group interaction (Kendon, 1967 ; Harrigan and Steffen, 1983 ; Streeck, 2014 ), seven studies video recorded both each participant plus the whole group interaction (Kalma, 1992 ; Novick et al, 1996 ; Brône et al, 2017 ; Kendrick and Holler, 2017 ; Auer, 2018 ; Weiss, 2018 ; Zima et al, 2019 ), two studies only video recorded two out of three participants and eye tracked the third participant (Jokinen et al, 2009 , 2013 ), one study used two cameras to capture interactions in Italian language and only one camera to capture interactions in Tzeltal and Yeli Dnye languages Rossano et al ( 2009 ). Eleven studies used camera-based eye tracking technology ( Table 4 ), which permits investigators to measure participant's visual behavior by detecting and tracking movement of different parts of the eye (see review: Morimoto and Mimica, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Goodwin (1981, 2000) extended these findings to multi-party interaction and found that prospective speakers have to secure the gaze of at least one recipient before they can take the turn. The imbalance between recipient’s gaze at the speaker and the speaker’s license to look away from the recipient is also indirectly confirmed by the way in which overlapping talk is resolved; here, the successful competitor for the floor tends to look away, that is to display a gaze pattern which is typical of a speaker, not of a recipient (see Zima et al, 2019).…”
Section: Turn-taking and Gazementioning
confidence: 88%
“…Atypically low attention to other people’s faces—and, more particularly, to the eye region—is one of the most documented diagnostic criteria for autism spectrum disorder [ 1 : 50], which is used in screening tools [ 2 ] and diagnostic assessments [ 3 ]. Facial expression and gaze play a crucial role in several areas that are known to be affected in autism: language development [ 4 ], joint attention [ 5 ], face and emotion recognition [ 6 ], mentalizing [ 7 ] and conversation management [ 8 ]. Yet, despite substantial research on social processing in autism, three crucial issues about the way autistic adults 1 explore faces remain outstanding: (a) Do autistic adults prefer looking at mouths over eyes?…”
Section: Introductionmentioning
confidence: 99%